Peningkatan Kapasitas Produksi Petani Kopi Republik Tani Mandiri - Hadi, Yuswono; Widiamsa, Adam Edward; Oktiarso, Teguh; Purnomo, Purnomo (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2022)
Republik Tani Mandiri (RTM) is group coffee farmers residing at Desa Kucur, Kab. Malang.The activity aimed to help RTM in increasing production capacity and train them to manage small business at early stage. Roasting process is the most critical process. After re-designing roasting machine and implementation, processing times reduce at 26,1%.